PERUBAHAN POLA KONSUMSI PANGAN KELUARGA PADA SEBELUM DAN SEWAKTU KRISIS EKONOMI - Yayah K. Husaini; Yekti Widodo; Agus Triwinarto; Salimar Salimar (Persagi, 2000)
CHANGES OF HOUSEHOLD CONSUMPTION PATTERN BEFORE AND DURING THE ECONOMIC CRISIS.Background: It is generally agreed that the economic crisis has an impact on food insecurity and malnutrition. People's ability to secure an adequate diet during the crisis in Indonesia would have been declined, however, data are not adequately available.Objective: The purpose of this study was to examine the magnitude of the impact of the crisis on household food consumption in three rural areas: Cianjur (West Java), South Lampung (Lampung) and Tanah Datar (West Sumatera).Method: The study on food consumption had been conducted in 1993/1994 (before crisis), and a similar study was repeated in 1999 during the peak of the crisis in the same areas. A total of 346 households in the three areas were surveyed. The food consumption was recorded using a 24- hour method; knowledge and attitudes on foods were collected by interview. Information on socio-cultural and tradition surrounding foods use were also gathered. The consumption of foods as part of the five groups (staples, plant and animal protein resources, vegetables, fruits, and milk) were examined, and ranked their frequencies of consumption and their contribution to each food groups. This would allow us to make comparison on household consumption patterns in the three different areas at before and during the peak of the crisis.Results: Rice was eaten two or three times a day and there was no significant changes in the frequency of consumption of rice during the crisis. Noodes and flours were eaten less frequent, but com and cassava were increased during the crisis. Although during the crisis there was a decrease in the consumption of meat, but not the case for fresh fish, salted fish, eggs, tofu and tempeh. People's have had switched the consumption pattern more on less expensive foods. People's in Tanah Datar (West Sumatera) was apparently better in coping mechanism as the response to the crisis than the other two areas. In Tanah Datar, diet was likely more diversified, perhaps even better than the situation at before crisis.Conclusions: The results suggest that the effects of the economc crisis on household food consumption were varied, depend on the nature (land) and environment, level of education, pattern of employment and socio-cultural in each areas.Key Words: economic crisis, consumption pattern, diet, coping mechanism